Late Pleistocene evolution of glacial Lake Purcell: a potential floodwater source to the Channeled Scabland - Peters, Jared Lee (2012)
The Quaternary history of the Channeled Scabland (CS) and its primary floodwater sources during marine isotope stage (MIS) 2 are well documented and understood. However, putative floodwaters from glacial lakes in British Columbia are poorly understood; these lakes may have supplied floodwaters to the CS in late MIS 2 during northward retreat of the Cordilleran Ice Sheet. This study combines geomorphology, sedimentology, stratigraphy, aerial photograph interpretation, ground penetrating radar, and geographic information science to reconstruct the paleogeography and evolution of glacial Lake Purcell in the Purcell Trench. Glacial Lake Purcell was a proglacial, ice-contact lake that was ~90 km long, up to 12 km wide, and ~360 m deep against its dam (Purcell Lobe). It contained >70 km3 of water just prior to drainage. It likely drained catastrophically (~47 km3 of water) down the Kootenay River valley into the Columbia River, though geomorphic evidence is equivocal.